Drug Discovery Research: New Frontiers in the Post-Genomic Era
Post Genomics Drug Discovery and Research explores and discusses some of the most important topics in post-genomics life and biopharmaceutical sciences. It provides an introduction to the field, outlining examples of many techniques currently used, as well as those still under development, which are important for the research of biopharmaceutical discovery in the post-genomics era.* Integrates several developing and cutting-edge technologies and methods like bioinformatics, experimental therapeutics, and molecular recognition* Includes discussion on topics such as: computer-aided ligand design; peptide and protein chemistry and synthesis; synthesis of active natural products; and the use of emerging technologies like proteomics, nanotechnology, or bioengineering.